Risk factors for anxiety and depression among pregnant women during the COVID-19 pandemic: A web-based cross-sectional survey. Issue 30 (24th July 2020) - Kajdy, Anna; Feduniw, Stepan; Ajdacka, Urszula; Modzelewski, Jan; Baranowska, Barbara; Sys, Dorota; Pokropek, Artur; Pawlicka, Paulina; Kaźmierczak, Maria; Rabijewski, Michał; Jasiak, Hanna; Lewandowska, Roksana; et al.
Abstract: Introduction: The article presents a protocol of a cross-sectional study of mental health of pregnant women in relation to the coronavirus disease 19 (COVID-19) pandemic. The primary aim is to compare differences in anxiety and depression scores of pregnant women between countries affected by the COVID-19 pandemic. The secondary aim is to assess demographic, economic, and social aspects affecting maternal anxiety and depression scores among pregnant women worldwide in the time of the COVID-19 pandemic. Finally, we will be able to compare differences in perception of the different aspects of the COVID-19 pandemic (social distancing, restrictions related to delivery) between countries and according to the epidemic status (number of infected patients, number of reported deaths). The comparisons will also be done according to the COVID-19 status of the participants. Methods and analysis: It is a web-based anonymous survey of pregnant women living in countries affected by the COVID-19 pandemic. The survey is comprised of 3 sections: Questions related to general demography, pregnancy health history, mental health history, socioeconomic factors, as well as perception of fear, burden and restrictions related to the COVID-19 pandemic; General Anxiety Disorder-7 (GAD-7) questionnaire for anxiety assessment and; Patient Health Questionnaire–9 (PHQ-9) for depression assessment. Web-based recruitment for health research has proven to be cost-effective and efficient. At current times with the COVID-19 pandemic, limited resources and social distancing restrictions, performing a mental health study involving pregnant women on a large international scale cannot be safely conducted without involving social-media. The fears of pregnant women fall into 3 categories: the medical condition, the economic status and the organization of daily activity. The study has received approval of the medical ethics committee and has been registered on Clinicaltrials.gov. Results will be published in peer-reviewed journals and made public through all available media. Abstract : Supplemental Digital Content is available in the text